(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Cloud computing is an approach to convey IT services on request and pay per utilization, and it can stores gigantic measure of data. Clients just consider how to spare their very own touchy data from being taken and when they use encryption algorithms like RSA Encryption Algorithm or Triple DES Encryption Algorithm, time for encrypting or decrypting encrypted data is longer. RSA is a cryptography technique used to encrypt and decrypt data, RSA is a hilter kilter cryptographic algorithm, which means that companies must use two separate keys to encrypt data, one is a public key, and the other is a secret key. RSA is generally a moderate encryption algorithm. Interestingly, Data Centric Security (DCS) is a developing methodology that expects to give data proprietors full control of their data security from inside the data itself, all through the data’s lifecycle on the cloud.